GEOKIMIA ORGANIK FRAKSI AROMATIK LIGHT OIL PRODUK PENCAIRAN BATUBARA AREA (PIT) BINTANG SANGATTA KALIMANTAN TIMUR - Lukman Sugiharto Wijaya; R. Y. Perry Burhan (2477 - 6165, 2016)
Character geochemical of Coal in area (pit) Stars Sangatta, East Kalimantan shows that the coal is classified as steam coal with thermal maturity and have low calories (5768 kcal/kg). The coal is melted in the 1L autoclave for 60 minutes at a temperature of 450oC and a pressure of 12 MPa to obtain a product slurry. Fractionation of slurry product based on boiling point using a vacum distillation apparatus 10 mmHg. Fractions obtained include naphtha, light oil, middle oil, heavy oil and coal liquid bottom. Data show that the weight percentage of the product melting fraction is dominated by heavy oil and coal liquid bottom with percentage of total> 50%. Fraction of light oil in the fractionation further by TLC and the eluent n-hexane in order to obtain an aromatic fraction. The composition of the aromatic hydrocarbon fraction light oil products were characterized using gas chromatography mass spectrophotometer (GC-MS). The identification shows that derivative of kadalen compounds, that is compounds norkadalen (C14H16) which is the fraction of oil that can be potentially as diesel fuel.